2020
DOI: 10.1002/ese3.721
|View full text |Cite
|
Sign up to set email alerts
|

Study on induced stress of hydraulic fracturing in fractured‐porous elastic media

Abstract: The study on induced stress of hydraulic fracturing is an important part of hydraulic fracturing design, temporary plugging and steering fracturing design, and completion design in oil and gas development. Based on fracture continuum method (FCM), cohesive unit method, and finite volume method (FVM), the propagation behavior of multiple hydraulic fractures (HFs) in fractured‐porous media reservoir is simulated from the perspective of fluid and geological stress coupling. The influence of natural fractures (NFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For unconventional reservoirs, especially low-permeability fractured reservoirs, under certain conditions, hydraulic fracturing can take advantage of developed NFs and the coupling effect of fluid flow and geological stress to form a highly permeable fracture network. [3][4][5][6] Microseismic field data confirmed that some reservoir fracture zones can be formed after hydraulic fracturing. 7 The corresponding capacity analysis showed that the larger the SRV, the larger the initial capacity.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…For unconventional reservoirs, especially low-permeability fractured reservoirs, under certain conditions, hydraulic fracturing can take advantage of developed NFs and the coupling effect of fluid flow and geological stress to form a highly permeable fracture network. [3][4][5][6] Microseismic field data confirmed that some reservoir fracture zones can be formed after hydraulic fracturing. 7 The corresponding capacity analysis showed that the larger the SRV, the larger the initial capacity.…”
Section: Introductionmentioning
confidence: 79%
“…In the development of shale, tight oil, and tight gas, and in the refracturing of old wells, hydraulic fracturing technology is generally adopted for reservoir reconstruction. For unconventional reservoirs, especially low‐permeability fractured reservoirs, under certain conditions, hydraulic fracturing can take advantage of developed NFs and the coupling effect of fluid flow and geological stress to form a highly permeable fracture network 3‐6 . Microseismic field data confirmed that some reservoir fracture zones can be formed after hydraulic fracturing 7 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 8 shows the seam roof stress cloud diagram of water injection for 200 seconds, 800 seconds, 1000 seconds, and 2000 seconds during the first hydraulic fracturing, and the stress accumulation and stress transfer of the coal roof during the entire fracturing process. 34 At the beginning of fracturing, the coal seam is still in the stage of water pressure accumulation, and the roof is less affected by water injection, and only the stress around the water injection hole increases. As the fracturing progresses, the stress rapidly increases in the area centered on the water injection hole and results in a stress concentration zone.…”
Section: Analysis Of Stress Change Of Coal Roofmentioning
confidence: 99%